Characterization of γδT cells in lung of Plasmodium yoelii-infected C57BL/6 mice - Haixia Wei; Chenxi Jin; Anping Peng; Hongyan Xie; Shihao Xie; Yuanfa Feng; Anqi Xie; Jiajie Li; Chao Fang; Quan Yang; Huaina Qiu; Yanwei Qi; et al. (Malaria Journal, 2021)
Abstract Background Malaria has high morbidity and mortality rates in some parts of tropical and subtropical countries. Besides respiratory and metabolic function, lung plays a role in immune system. γδT cells have multiple functions in producing cytokines and chemokines, regulating the immune response by interacting with other cells. It remains unclear about the role of γδT cells in the lung of mice infected by malaria parasites. Methods Flow cytometry (FCM) was used to evaluate the frequency of γδT cells and the effects of γδT cells on the phenotype and function of B and T cells in Plasmodium yoelii-infected wild-type (WT) or γδTCR knockout (γδT KO) mice. Haematoxylin-eosin (HE) staining was used to observe the pathological changes in the lungs. Results The percentage and absolute number of γδT cells in the lung increased after Plasmodium infection (p < 0.01). More γδT cells were expressing CD80, CD11b, or PD-1 post-infection (p < 0.05), while less γδT cells were expressing CD34, CD62L, and CD127 post-infection (p < 0.05). The percentages of IL-4+, IL-5+, IL-6+, IL-21+, IL-1α+, and IL-17+ γδT cells were increased (p < 0.05), but the percentage of IFN-γ-expressing γδT cells decreased (p < 0.05) post-infection. The pathological changes in the lungs of the infected γδT KO mice were not obvious compared with the infected WT mice. The proportion of CD3+ cells and absolute numbers of CD3+ cells, CD3+ CD4+ cells, CD3+ CD8+ cells decreased in γδT KO infected mice (p < 0.05). γδT KO infected mice exhibited no significant difference in the surface molecular expression of T cells compared with the WT infected mice (p > 0.05). While, the percentage of IFN-γ-expressing CD3+ and CD3+ CD8+ cells increased in γδT KO infected mice (p < 0.05). There was no significant difference in the absolute numbers of the total, CD69+, ICOS+, and CD80+ B cells between the WT infected and γδT KO infected mice (p > 0.05). Conclusions The content, phenotype, and function of γδT cells in the lung of C57BL/6 mice were ...